The influence of digital branding strategies on consumer engagement: Evidence from Malaysia’s retail sector - Lasi, Masri Bin Abdul (Asian Journal of Empirical Research, 2025)
Digital branding has become a cornerstone of consumer engagement strategies in the modern retail landscape. In Malaysia’s rapidly evolving retail sector, brands are increasingly adopting digital tools to connect with consumers, influence perceptions, and foster brand relationships. This study investigates the impact of digital branding components brand visibility, interactivity, content value, and consistency on consumer engagement across online retail platforms. Drawing upon branding theory and consumer behavior frameworks, the research employs a quantitative approach, surveying 400 online retail consumers in Malaysia. Data were analyzed using SPSS, with results indicating that brand interactivity and content value had the strongest positive influence on cognitive and emotional engagement, while brand consistency also contributed significantly to behavioral engagement. However, brand visibility alone did not guarantee deeper consumer involvement without complementary interactive or personalized content. These findings provide empirical evidence supporting the integration of value-driven content and two-way brand communication in digital strategy. The study offers both theoretical enrichment in digital branding literature and practical implications for retailers aiming to cultivate stronger consumer-brand relationships through digital platforms. Recommendations for future research include extending the model across different sectors and incorporating longitudinal design to assess evolving engagement behaviors in digital contexts.